Low Frequency of Early Complications With Dual‐mobility Acetabular Cups in Cementless Primary THA. Issue 10 (October 2016) - Chughtai, Morad; Mistry, Jaydev B.; Diedrich, Aloise M.; Jauregui, Julio J.; Elmallah, Randa K.; Bonutti, Peter M.; Harwin, Steven F.; Malkani, Arthur L.; Kolisek, Frank R.; Mont, Michael A.
Abstract: Background: Dislocation complicates 1% to 5% of primary total hip arthroplasties (THAs). As a result, some surgeons consider dual‐mobility articulations, which are usually used in the revision setting to decrease the likelihood of dislocation, as an option for primary THA. However, few studies have evaluated their use in this setting. Questions/purposes: (1) What is the cup survivorship when the dual‐mobility articulation is used in the setting of primary THA? (2) What are the clinical outcomes with this approach? (3) What are the radiographic outcomes? (4) What are the complications of dual‐mobility articulations in primary THA? Methods: Between 2011 and 2013, the five participating surgeons performed 495 cementless primary THAs. During that time, one of the five surgeons used dual‐mobility articulations for all THAs, and the other four used it whenever the acetabular cup size was 52 mm or greater to enable a 28‐mm head. Of the 495 patients, 453 (92%) were performed using this device. Smaller patients were treated with a standard THA. Of the 453 patients, a total of 43 patients (10%) were lost to followup before the 2‐year minimum. The resulting 410 patients who were included in the analysis (164 men, 246 women) had a mean age of 64 years (SD, 12 years). The mean followup was 3 years (SD, 0.7 years). We performed Kaplan‐Meier analyses to assess survivorship to aseptic failure and all‐cause acetabular component survivorship. Clinical outcomes were evaluated using the Harris hip score (HHS); radiographs were assessed for cup migration, progressive radiolucencies, and positional changes of the components; and any surgery‐related complications were recorded. Results: The survivorship to aseptic failure and all‐cause acetabular component survivorship was 99.8% (failures, n = 1) (95% confidence interval [CI], 4.517‐4.547) and 99.3% (failures, aseptic, n = 1; septic, n = 2) (95% CI, 4.494‐4.543); one hip had trunnion notching caused by impingement of a malpositioned cup, which was treated with revision of the cup and stem; and two patients had periprosthetic infections that were treated with two‐stage revisions. There were no dislocations. Patients had a mean HHS of 94 (SD, 6) at final followup. On radiographic evaluation, no progressive radiolucencies or positional changes of the components were identified. Surgical complications included one traumatic avulsion of the abductors, one traumatic avulsion of the greater trochanter, which was repaired without revision of any of the components, and one loose femoral stem, which required revision of the femoral component only. Conclusions: Dual‐mobility cups in primary THA yield seemingly comparable survivorship and complications to conventional THA bearings at short‐term followup. Because serious complications have occasionally been reported with the use of these bearings, larger, longer term, comparative‐and ideally, randomized‐trials will be needed to establish the superiority of one approach over the other. Until or unless such studies show the superiority of dual‐mobility designs for primary THA, we recommend that in the setting of uncomplicated primary THA, dual‐mobility articulations be used only in centers that track their results carefully or in research protocols. Level of Evidence: Level IV, therapeutic study.